Living together with difference : narratives and practices of co-existence in Armenian-Azerbaijani rural communities in Georgia - Romashov, Vadim; Rauhan- ja konfliktintutkimuskeskus (TAPRI studies in peace and conflict research / Tampere Peace Research Institute, University of Tampere, ISSN 1459-5184, 2022)
Tiivistelmä.
Keywords: kyläyhteisöt; maaseutuyhteisöt; yhteisöllisyys; etnografia; arki; vuorovaikutus; rinnakkaiselo; ryhmien väliset suhteet; armenialaiset; azerit; sosiaaliantropologia; rauhantutkimus; Georgia